Improved outcomes in rheumatoid arthritis with obesity after a weight loss intervention: randomized trial. (28th May 2022) - Ranganath, Veena K; La Cava, Antonio; Vangala, Sitaram; Brook, Jenny; Kermani, Tanaz A; Furst, Daniel E; Taylor, Mihaela; Kaeley, Gurjit S; Carpenter, Catherine; Elashoff, David A; Li, Zhaoping
Abstract: Objective: To examine whether a weight loss intervention programme improves RA disease activity and/or musculoskeletal ultrasound synovitis measures in obese RA patients. Methods: We conducted a proof-of-concept, 12-week, single-blind, randomized controlled trial of obese RA patients (BMI ≥ 30) with 28-joint DAS (DAS28)  ≥ 3.2 and with evidence of power Doppler synovitis. Forty patients were randomized to the diet intervention ( n  = 20) or control group ( n  = 20). Diet intervention consisted of a hypocaloric diet of 1000–1500 kcal/day and high protein meal replacements. Co-primary outcomes included change in DAS28 and power Doppler ultrasound (PDUS)-34. Clinical disease activity, imaging, biomarkers, adipokines and patient-reported outcomes were monitored throughout the trial. Recruitment terminated early. All analyses were based on intent-to-treat for a significance level of 0.05. Results: The diet intervention group lost an average 9.5 kg/patient, while the control group lost 0.5 kg ( P  < 0.001). Routine Assessment of Patient Index Data 3 (RAPID3) improved, serum leptin decreased and serum adiponectin increased significantly within the diet group and between the groups (all P  < 0.03). DAS28 decreased, 5.2 to 4.2, within the diet group ( P  < 0.001; −0.51 [95% CI −1.01, 0.00], P  = 0.056, between groups). HAQ-Disability Index (HAQ-DI) improved significantly within the diet group ( P  < 0.04; P  = 0.065 between group). Ultrasound measures and the multi-biomarker disease activity score did not differ between groups (PDUS-34 −2.0 [95% CI −7.00, 3.1], P  = 0.46 between groups). Conclusion: Obese RA patients on the diet intervention achieved weight loss. There were significant between group improvements for RAPID3, adiponectin and leptin levels, and positive trends for DAS28 and HAQ-DI. Longer-term, larger weight loss studies are needed to validate these findings, and will allow for further investigative work to improve the clinical management of obese RA patients. Trial registration: ClinicalTrials.gov, https://clinicaltrials.gov, NCT02881307